Access and knowledge of contraceptives and unmet need for family planning in Pakistan - Muhammad Farhan Asif; Majid Ali; Hafiz Ghulam Abbas; Tayyaba Ishfaq; Shafaqat Ali; Ghulam Abid; Zohra S. Lassi (BMC Women's Health)
Abstract Background Family planning facilities provide an extensive choice of assistance that is beneficial for women and the society. It may limit the fatality risk for mothers and babies by reducing the rate of pregnancies and abortions. The Government of Pakistan has been continuously trying to persuade the people about the importance of family planning. The accomplishment of these programs depends upon various aspects associated with the knowledge, availability, and access to contraceptives. This paper has investigated the effect of knowledge and access to contraceptives on the unmet need for family planning (UMNFP) among married women of reproductive age (MWRA) in Pakistan. Method The comprehensive dataset of the Pakistan Demographic and Health Survey 2017-18 has been used to investigate the effect of knowledge and access to contraceptives on UMNFP among MWRA in Pakistan by applying Multivariable Logistic regression. Results The prevelance of UMNFP is higher among MWRA of 25 to 34 years than other age groups. The likelihood of UMNFP decreases with increase in education above the primary level. The prevalence of UMNFP is found higher among women who belong to the poorer wealth quintile than the women of the poorest wealth quintile. The odds of UMNFP are considerably low among women belonging to the richer and richest wealth quintile, compared to the women of the poorest wealth quintile. Women’s participation in decision making for not using contraceptives is a significant factor to reduce UMNFP. The odds of UMNFP are higher among those women who have no knowledge and lack of access to contraceptives compared to those who have knowledge and access to contraceptives. Conclusions Both knowledge and access to contraceptives are important factors to determine UMNFP. The government should initiate programs to disseminate knowledge as well as provision of contraceptives for effective family planning.